Pemanfaatan Media Sosial Instagram @Sahabat_umkm: Studi Uses and Gratification Sebagai Upaya Edukasi Pelaku Usaha Mikro - Pratama, Muhammad Tarel Rizky; Pamungkas, Indra Novianto Adibayu; Pramesthi, Jasmine Alya (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2024)
Digitalization is increasingly advancing, and one manifestation of this progress is the emergence of the social media platform Instagram. Micro-business owners utilize Instagram to meet their needs (uses and gratification), particularly in seeking education for micro-business ventures. One of the accounts disseminating education for micro-businesses is @sahabat_umkm. The objective of this research is to measure the extent of the influence of utilizing Instagram @sahabat_umkm: a study on uses and gratification as an effort in educating micro-business owners. The research method employed is causal quantitative. Data analysis techniques include Pearson product-moment correlation analysis, t-test, simple linear regression analysis, and coefficient of determination test. The data was collected by the researcher online using a questionnaire and distributed to 399 respondents who are followers of Instagram @sahabat_umkm. The sampling technique used by the researcher is Nonprobability Sampling, specifically Purposive Sampling. The result of the Pearson product-moment correlation analysis is 0.472, indicating a moderate to strong relationship between the variables of Instagram utilization and the effort in educating micro-business owners. Additionally, the magnitude of the influence on the variable of Instagram @sahabat_umkm utilization on the variable of effort to educate micro-business owners is 22.2%, while 72.8% is influenced by other factors beyond this study. The results of the simple linear regression analysis indicate that every one-unit increase in the Instagram @sahabat_umkm utilization variable corresponds to an increase of 0.231 in the variable of effort to educate micro-business owners. Through this research, it is proven that the utilization of Instagram @sahabat_umkm (variable X) significantly and positively impacts the effort to educate micro-business owners (variable Y).